Genetic screen in myeloid cells identifies TNF-α autocrine secretion as a factor increasing MDSC suppressive activity via Nos2 up-regulation - Schröder, Matthias; Krötschel, Marit; Conrad, Lena; Naumann, Svenja Kerstin; Bachran, Christopher; Rolfe, Alex; Umansky, Viktor; Helming, Laura; Swee, Lee Kim (Scientific reports, 2018)
The suppressive microenvironment of tumors remains one of the limiting factors for immunotherapies. In tumors, the function of effector T cells can be inhibited by cancer cells as well as myeloid cells including tumor associated macrophages and myeloid-derived suppressor cells (MDSC). A better understanding of how myeloid cells inhibit T cell function will guide the design of therapeutic strategies to increase anti-tumor responses. We have previously reported the in vitro differentiation of MDSC from immortalized mouse hematopoietic progenitors and characterized the impact of retinoic acid and 3-deazaneplanocin A on MDSC development and function. We describe here the effect of these compounds on MDSC transcriptome and identify genes and pathway affected by the treatment. In order to accelerate the investigation of gene function in MDSC suppressive activity, we developed protocols for CRISPR/Cas9-mediated gene editing in MDSC. Through screening of 217 genes, we found that autocrine secretion of TNF-α contributes to MDSC immunosuppressive activity through up-regulation of Nos2. The approach described here affords the investigation of gene function in myeloid cells such as MDSC with unprecedented ease and throughput.